Development Of Neem Modified ZnO Photocatalyst Incorporated LDPE For Antimicrobial Application - Woo, Wei Jin (Universiti Sains Malaysia, 2018)
In recent years, healthcare-associated infections are rising concerns as the susceptible attack of harmful microbes may cause death to patients. ZnO was known with its antimicrobial properties and LDPE is commonly used in biomedical field but the study on antimicrobial properties of ZnO incorporated LDPE was not comprehensively investigated. Thus, this research project aims to develop stabilized ZnO particles incorporated into LDPE for antimicrobial application. The ZnO is stabilized using PVA by sonication method and neem extraction is added in using methanol reflux method. It is found out that PVA can stabilized ZnO and neem extraction further enhance the distribution of the ZnO. The stabilized particles were incorporated into LDPE matric by injection moulding, and LDPE/ZnO/PVA/10% neem portraits the lowest crystallinity (42.61%). Photocatalytic and scavenger test confirmed release of ROS and Zn2+ ions released is confirmed by ICP test, which contributes to the antimicrobial properties. Lastly, under the protocol of ASTM E2149, the LDPE/ZnO/PVA/10% neem portraits antibacterial properties with 98.56% reduction of gram negative E.coli bacteria in 72 hours.